Experimental investigation for the friction evaluation in the masonry structures. (2016) - Olivito, R.S.; Esposito, M.; Totaro, N.
In the scientific literature on historic static masonry, the term 'friction' is sporadically mentioned to justify certain phenomena: "removing friction, neglecting friction, ...". Recent studies have shown that in some static situations the friction factor can play a crucial role in the equilibrium, considering the intrinsic value of the gravitational force of traditional vector systems. In this regard, the thesis and the experiments in De Zarlo (2008) and in Lanzino (2008) are an interesting attempt to highlight the importance of the role of friction in masonry structures. This work wants to study both from the point of view of experimental and theoretical the assessment of the friction forces occurring in the equilibrium of the masonry elements. Only in the arches and domes made with the technique of overhanging, the frictional forces play a hidden but decisive role. Starting by some heuristic experiments this paper advances a series of results and observations leading to the investigation of a theory on static overhanging domes that is independent of the membrane theory. This paper points out the complex problem of friction in masonry structures having recourse to simple experimental models aiming to the determination of friction, also using the Coulomb theory on friction.